Respostas
respondido por:
4
a1 = -6
a2 = -9
r = a2 - a1 = -9 - (-6) = -9 + 6 = -3
an = -66
Termo geral: an = a1 + (n - 1).r
-66 = -6 + n - 1).-3
-66 = -6 - 3n + 3
3n = 66 - 6 + 3
3n = 63
n = 63/3
n = 21
Resposta: 21 termos
Espero ter ajudado.
a2 = -9
r = a2 - a1 = -9 - (-6) = -9 + 6 = -3
an = -66
Termo geral: an = a1 + (n - 1).r
-66 = -6 + n - 1).-3
-66 = -6 - 3n + 3
3n = 66 - 6 + 3
3n = 63
n = 63/3
n = 21
Resposta: 21 termos
Espero ter ajudado.
respondido por:
0
An=a1+(n-1)r
-66=-6+(n-1)(-3)
-66+6=(n-1)(-3)
-60=n-1
3
-20+1=n
n=-19
-66=-6+(n-1)(-3)
-66+6=(n-1)(-3)
-60=n-1
3
-20+1=n
n=-19
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás